Penelitian Teologi Pastoral: Penghayatan Iman Umat di Kota Surabaya di Tengah Masa Pandemi - Setiawan, Krisna; Satrio, Leonardus (Felicitas, 2021)
The Covid-19 pandemic has paralyzed almost all sectors of people's lives, including religious life. A series of social restriction policies were carried out to reduce the rate of increase in the number of victims. In line with that, the Catholic Church of the Diocese of Surabaya decided a policy to stop all forms of mass activity. This creates a greater distance between the people and their shepherd. This research was conducted to determine the appreciation of the faith of the people in the city of Surabaya in the midst of the pandemic. Thus, the results and analysis of this study can be taken into consideration for more relevant pastoral policies during the pandemic.